(untitled) (Journal of Oriental Studies, 2022)
This study examines the efforts made by the Iraqi scholar Mohsen Mahdi in the field of studying Farabi philosophy, and the reasons that led him to specialize in the thought of Abu Nasr al-Farabi, who is considered the founder of Islamic philosophy, and one of the most important and influential Muslim philosophers in the philosophy of Middle ages. The study then analyzed the methodological perspective on which Dr. Mohsen Mahdi relied in looking at Al-Farabi’s philosophical achievement. This perspective is based on two things, the first is fairness and the second is exploration. Mohsen Mehdi found in Al-Farabi his deepening into the beginning of language, its completeness and its relationship with philosophy and religion in the book (Letters), his greatest work. A common opinion before Mohsen Mehdi published his book On letters was that philosophers who wrote in Arabic explored the meaning of this term in the same way as Greek philosophers. Keywords: Al-Farabi ,exploration, fairness, Mahdi, letters, philosophy.